2016
DOI: 10.5424/sjar/2016141-7450
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of legume seeds as ingredients in animal feed

Abstract: competition of feedstock proteins produced mainly in North and South America; the increased use of chemical fertilizers in crop production; the availability of cheap sources of animal protein (fish and meat-beef, pork and poultry), and the simplification of agricultural systems. In fact, during the last decades the cultivation of grain legumes in Europe, as well as their use, fell sharply: in 2010 the total production of pulses in Europe was 39% of that obtained in 1990 (FAO Stat: http://faostat3.fao.org/home/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…In seeds of other economically important Vicia species-V. sativa (common vetch) and V. ervilia (bitter vetch), the content of RFOs was two-fold and ca 10-fold lower (respectively) than in V. narbonensis (Table 1). The high level of RFOs in V. narbonensis, found in our study (Tables 1, 2), is consistent with results obtained by Rolletschek et al (2002) and Martín-Pedrosa et al (2016). In a wild type of V. narbonensis, the level of RFOs was 70.2 mg g -1 dry mass, whereas in lines with a disrupted starch biosynthesis pathway, the level of RFOs increased up to 94 mg g -1 dry mass (Rolletschek et al 2002).…”
Section: The Content Of Soluble Carbohydrate In Seedssupporting
confidence: 91%
See 2 more Smart Citations
“…In seeds of other economically important Vicia species-V. sativa (common vetch) and V. ervilia (bitter vetch), the content of RFOs was two-fold and ca 10-fold lower (respectively) than in V. narbonensis (Table 1). The high level of RFOs in V. narbonensis, found in our study (Tables 1, 2), is consistent with results obtained by Rolletschek et al (2002) and Martín-Pedrosa et al (2016). In a wild type of V. narbonensis, the level of RFOs was 70.2 mg g -1 dry mass, whereas in lines with a disrupted starch biosynthesis pathway, the level of RFOs increased up to 94 mg g -1 dry mass (Rolletschek et al 2002).…”
Section: The Content Of Soluble Carbohydrate In Seedssupporting
confidence: 91%
“…Similarly low levels of RFOs were estimated recently by Martín-Pedrosa et al (2016) in seeds of two bitter vetch cultivars. Such a low level of RFOs is unique among legumes (Kadlec et al 2001).…”
Section: Sectionsupporting
confidence: 67%
See 1 more Smart Citation
“…Due to its nutritive value, besides the fact that this crop is not usually used for human consumption, Narbon beans have been traditionally used for animal feeding as an interesting alternative to reduce the high dependence of soybean [8]. Del Pino-García et al [9] reported results on the bioactive properties of Vicia narbonensis and demonstrated the need to select certain varieties to reduce the presence of the antinutrient g-glutamyl-S-ethenyl-cysteine (GEC), a sulfur-containing dipeptide [10][11][12]. Active breeding and research programs have been developed in recent years to reduce the GEC content in Narbon beans and provide information for establishing the limits of inclusion of this grain legume in feed formulations, which are set at 10-12.5%, although a GEC acceptance threshold for different species has not yet been defined [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Del Pino-García et al [9] reported results on the bioactive properties of Vicia narbonensis and demonstrated the need to select certain varieties to reduce the presence of the antinutrient g-glutamyl-S-ethenyl-cysteine (GEC), a sulfur-containing dipeptide [10][11][12]. Active breeding and research programs have been developed in recent years to reduce the GEC content in Narbon beans and provide information for establishing the limits of inclusion of this grain legume in feed formulations, which are set at 10-12.5%, although a GEC acceptance threshold for different species has not yet been defined [11,13]. In the context of human nutrition and within a varied and well-balanced diet, Narbon bean could be an excellent source of vegetable nutrients and bioactive components, although advances in the selection of the most suitable cultivars for this aim are required.…”
Section: Introductionmentioning
confidence: 99%